KAPASITAS PERILAKU PROMOSI DAN PERANAN AKTOR DALAM PENGEMBANGAN DESA WISATA BERBASIS KOMUNITAS (STUDI KASUS DESA WISATA CINUNUK): STUDI KASUS DESA WISATA CINUNUK - Nabiela Rizki Alifa (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2022)
Global and national economic challenges require various sectors of the economy to prepare including the tourism sector. Based on data from Bappenas which states the target of tourism villages in the 2020-2024 National Medium-Term Development Plan (RPJMN) is 244 villages.. It’s in line with the Direction of the President and Vice President of the Republic of Indonesia regarding Tourism and Creative Economy in 2021. The development of this tourism village requires the role of the community, which means that the community is not only a resident of tourist objects, but also a tourist actor, because the sustainability of the tourist village depends on tourist visits. This study is conducted to analyze the relationship between the promotional behavior capacity of local people as internal actors and the relationship between the role of actors and tourist visits. The research was conducted in Cinunuk Tourism Village with a quantitative approach and supported by qualitative data. The results showed that there is a significant relationship between the capacity of promotional behavior and the role of internal actors and also a significant relationship between the role of actors both internal and external with tourist visits. For this reason, efforts are needed to maximize the potential of existing promotional activities.